Penerapan Metode Diskusi Siswa Kelas IV pada Mata Pelajaran IPA SD Negeri Sewon Bantul Yogyakarta - Fifi Kharismah; Henry Aditya Rigianti (Program Studi PGSD STKIP PGRI Banjarmasin, 2023)
This research is motivated by the low understanding of learning methods that are not in accordance with the learning material. As a teacher, you should be good at choosing methods, techniques, and learning models so that the teaching and learning process can take place actively, creatively, effectively, and fun. While the obstacles from students include: low student motivation; student creativity in learning is still lacking. To improve students' competence in understanding the concept of root parts and their functions, it is necessary to use the